Spinal Cord Stimulation After Chronic Complete Spinal Cord Injury Enables Volitional Movement Even in Absence of Stimulation. (16th November 2020) - Freeman, David; Sturtevant, Dylan; Pino, Isabela P; Netoff, Theoden; Parr, Ann M; Darrow, David P
Abstract: INTRODUCTION: Spinal cord injury (SCI) is a devastating neurologic injury that can be a cause of paralysis. Spinal cord stimulation (SCS) has been reported to partially restore functions for patients who have chronic neurologically complete spinal cord injury. In the E-STAND (Epidural Stimulation After Neurologic Damage) trial we have demonstrated some of these previous results without any rehabilitative therapy or locomotor training. Recently we have observed that a subset of subjects have developed restoration of volitional movement with stimulation off. METHODS: Four of the currently enrolled patients in the ESTAND trial exhibited volitional movement without stimulation. Volitional movement was assessed with the Brain Motor Control Assessment (BMCA) using EMG recordings and visual examination at baseline and follow up visits with and without stimulation. Additional assessment was performed with effort assisted cycling. RESULTS: Significant increases in volitional power were found between those observed to spontaneously move without stimulation and those unable ( P < .0005). The likelihood of recovery of spontaneous volitional control was correlated with spasticity scores prior to the start of eSCS therapy ( P = . 048). Volitional power progressively improved over time ( P = . 016). Additionally, cycling was possible without stimulation ( P < . 005). CONCLUSION: These findings supports previous studies suggesting "complete" spinal cord injury is likely not as common as previously believed, if it exists at all in the absence of transection and that preserved pathways are substrates for eSCS-mediated recovery in clinically motor-complete spinal cord injury. SCS after SCI may provide benefit beyond immediate stimulation that may facilitate and be amenable to rehabilitation in a generalizable patient population.